Support and Practice of Smoke-Free Eating Places in Sarawak, Malaysia: A Structural Path Analysis - Md Mizanur, Rahman; Mohd Taha, Arif; Abdul Rahim, Abdullah (Department of Public Health, Kermanshah University of Medical Sciences, 2022)
Background: Smoke-free eating places are effective in reducing exposure to secondhand smoke (SHS). Eateries should comply with implementing smoke-free eating-places under the Control of Tobacco Products Regulations 2018 in all open-air eating-places to reduce tobacco consumption to achieve the plan of having Malaysia free of tobacco by 2045. Objectives: To determine the impact of perceived knowledge on tobacco control law and SHS and attitude to support and practice smoke-free eating-places. Methods: A total of 620 respondents participated in this cross-sectional study. The eating-places were selected randomly from 5 administrative divisions of Sarawak. Data on perceived tobacco control law, knowledge of the effects of SHS on health and environment, attitude and support towards smoke-free eating-places, and current smoke-free eating-places were collected by face-to-face interview using a structured questionnaire. A partial least squares model was developed to examine the impact of knowledge, attitude, and support towards the smoke-free eating-places with the current practice of smoke-free eating-places. WarpPLS version 7.0 was used to examine the structural path and to test the hypothesis. Results: The structural path analysis revealed that perceived knowledge of tobacco control lawhad no impact on practicing smokefree eating-places (P > 0.05). However, the knowledge of the health and environmental effects of SHS had direct and indirect effects on attitude and support for smoke-free eating-places (P < 0.001). In addition, attitude towards smoke-free eating-places had a significant mediating effect on practicing smoke-free eating-places (P < 0.001). Besides that, supporting smoke-free eating-places had a significant direct impact on the practice of smoke-free eating-places (P < 0.001). Conclusions: Legislation and implementation of smoke-free eating-places along with the antismoking program and education efforts could support the cessation of tobacco use in all public places, including all eateries.